Designing a Leadership Capabilities Model for Organizational Service Productivity (Case Study: The Public Banking Sector in Iraq) - Al-Karaawi, Qasim Muhammad Abdul Ali; Aghasi, Saeid; Al Shamri, Ahmed Abdullah Amanah Salem; Davoodi, Sayyed Mohammad Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The aim of this study is to design and test a leadership capabilities model to enhance organizational service productivity, with a focus on the public banking sector in Iraq. Methodology: The research is applied in nature and uses a survey method. It is a qualitative study. The statistical population includes: a) executives in the banking industry, b) academic experts, and c) combined academic-executive experts in the banking industry in Iraq. The analysis was conducted using thematic analysis. The research tool was semi-structured interviews. Findings: The results indicate that out of 60 categories, seven dimensions were extracted, which include having strategic perspectives, possessing effective organizational communication, team management and leadership skills, having suitable personal characteristics, focusing on customer needs, the ability to facilitate changes, and possessing decision-making power. Conclusion: In conclusion, leadership skills, particularly human skills and strategic management, significantly influence organizational outcomes such as citizenship behavior, decision-making, and performance. Effective knowledge management and the fostering of transformational leadership are crucial for enhancing organizational performance, particularly in dynamic sectors like education and healthcare.